Therapeutic Benefit of Vernonia amygdalina in the Treatment of Diabetes and Its Associated Complications in Preclinical Studies - Du-Bois Asante; Gideon Akuamoah Wiafe (Journal of Diabetes Research)
Diabetes mellitus (DM), a complex heterogeneous metabolic disorder characterized by a defect in the function of insulin, is on the rapid rise globally. Sustained hyperglycemia which is a major sign of DM is linked to the generation of reactive oxygen species which promotes adverse complications of the disorder. Traditional herbal treatment of DM is a common practice in Africa and other tropical parts of the world. Vernonia amygdalina (VA), one of the highly researched species in the Asteraceae family, has proven to possess potent antidiabetic properties. Several phytochemicals identified in multiple extracts from VA are purported to be responsible for the antidiabetic potential of the plant. In this review, we discuss the therapeutic potential of VA in diabetes and its associated complications. We appraise the current evidence and further suggest potential areas that could be effectively exploited in future VA research on diabetes.